A Rapid Review Of Guidelines Of Instructional Operative Video - Makkiyah, Feda Anisah (Universitas Muhammadiyah Sumatera Utara, 2023)
Teaching skills are far more complex than teaching content. It needs framework, observation, and feedback. One of the popular media for learning operative procedures is video. However, the guidelines for instructional videos for surgical postgraduate students have not been established. This article tried to serve the rapid review of essential design principles to evaluate the quality of demonstration videos of procedural skills and also use the design principles in one video example. Methods: The rapid review was conducted according to Crawford's framework. Scopus was chosen as a single database. The inclusion criteria are full texts that discuss instructional videos and postgraduate medical learning skills. There were no language restrictions. Three articles were chosen from six that resulted from the literature search. The three articles are appraised based on the case-controlled or cross-sectional methodology by The Joanna Briggs Institute Critical Appraisal tools for use in JBI Systematic Reviews. Results: A total of six articles were retrieved, and the full text was reviewed for three pieces that met the study's criteria. Those articles were heterogenous in the design principles of instructional video. Two articles agreed on these points: short videos and step-by-step procedures with audio narratives. Another paper by Simon discussed several details aspects of the video, such as pathology, who are the operators in the video. Conclusions: Videos are a valuable educational tool for procedural skill knowledge acquisition and retention. Several important points should be embedded in the video, such as the step-by-step procedure and the short duration of the video. Future research needs to be carried out on establishing the guidelines of instructional videos to enhance the mastering of procedural skills.Keywords: Design, principles, procedures, surgery, video